The Effect of EQ on Mathematics Learning Achievement of MTs Islamiyah Medan Students - Hendra Utama Zein; Tanti Jumaisyaroh Siregar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The purpose of this study was to find out how emotional instability affects the mathematics learning ability of grade VIIIA Islamiyah Medan students. Based on the hypothesis proposed, there is evidence that the emotional instability of grade VIIIA Islamiyah Medan students has a positive effect on the ability to learn mathematics. The sample of this study amounted to 37 students of grade VIII A MTs Islamiyah Medan. This type of research uses ex post facto quantitative models. The research material was 25 emotional intelligence questionnaire surveys and five learning achievement test subjects. The data analysis techniques used combine descriptive analysis with simple regression additional strategies. The research findings showed that in general, the percentage of emotional stress in students of 43.3% fell into the high percentage category. While in general, 70.2% put the picture of students' mathematics learning outcomes in the medium category. The equation Y = 28.564 + 0.976X was obtained from the findings of the investigation using simple linear regression. Ha was approved and Ho was rejected. Based on the findings of the significance test which shows a significant value of 0.000 where the value is significant 0,05. It shows that emotional intelligence has an impact on students' ability to master mathematics.